Hydroarylation of N‐Allenyl Derivatives Catalyzed by Copper. Issue 48 (3rd November 2020) - Abed Ali Abdine, Racha; Pagès, Lucas; Taillefer, Marc; Monnier, Florian
Abstract : An additive‐free copper catalytic system was used to perform the addition of (hetero)aryl nucleophiles to N ‐allenyl derivatives. This intermolecular C–C bond formation occurs with both complete regio‐ and stereoselectivity to afford the linear ( E ) allylic product with moderate to excellent yields. This atom economical method is the first example of hydroarylation of allenes catalyzed by copper. Abstract : The regio‐ and stereoselective addition of (hetero)aryl nucleophiles to N ‐allenyl derivatives is described under copper catalysis. represents the first example of hydroarylation of allenes catalyzed by copper.